2015
DOI: 10.1039/c4ay02161d
|View full text |Cite
|
Sign up to set email alerts
|

Analytical characterization of a method for mercury determination in food using cold vapour capacitively coupled plasma microtorch optical emission spectrometry – compliance with European legislation requirements

Abstract: This paper presents the analytical characterization of a highly sensitive and inexpensive method for Hg determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…30,32 The reproducibility of the retention/desorption process of Hg on/from the gold lament was found to be better than 7%, and the direct heating of the lament (5 V, 1.5 A) provided a rapid desorption and a high ow rate of Hg vapour towards the plasma, and hence a high sensitivity. 30,32 The comparison method for SICV-mCCP-OES was CV-AFS with chemical Hg CV generation using 20% SnCl 2 solution stabilized in 15% HCl. Determinations were carried out using a fully automated Hydra-AF Mercury Analyzer, Teledyne Leeman Instruments (Hudson, USA).…”
Section: Instrumentationmentioning
confidence: 99%
See 3 more Smart Citations
“…30,32 The reproducibility of the retention/desorption process of Hg on/from the gold lament was found to be better than 7%, and the direct heating of the lament (5 V, 1.5 A) provided a rapid desorption and a high ow rate of Hg vapour towards the plasma, and hence a high sensitivity. 30,32 The comparison method for SICV-mCCP-OES was CV-AFS with chemical Hg CV generation using 20% SnCl 2 solution stabilized in 15% HCl. Determinations were carried out using a fully automated Hydra-AF Mercury Analyzer, Teledyne Leeman Instruments (Hudson, USA).…”
Section: Instrumentationmentioning
confidence: 99%
“…The high speed acquisition mode of the QE65 Pro Spectrometer soware was started simultaneously with Hg vapour release to record 10 spectral episodes, each with 500 ms integration time. 24,30,32 The spectra Playback Controls application of the microspectrometer soware showed that the Hg emission signal emerged during the 2 nd -4 th episodes, and consequently only the rst ve episodes were taken into account. The microspectrometer does not allow real-time emission measurements because the CCD detector has lower temporal resolution than a photomultiplier and cannot respond to fast changes of the signal in time.…”
Section: Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the atoms can be obtained by electrothermal evaporation in a graphite furnace (GF-AAS) or in a flame (F-AAS) [25][26][27]. Beside these, other non-conventional techniques can also be used to determine metal analytes in different samples [28][29][30]. For specific elements (i.e., Hg) which have high volatility, the direct measurement in solid samples (including zeolites) by thermal desorption is possible [31].…”
Section: Introductionmentioning
confidence: 99%